Development of a bioadhesive nanoformulation with Glycyrrhiza glabra L. extract against Candida albicans. Issue 8 (14th September 2018) - Roque, Luís; Duarte, Noélia; Bronze, Maria Rosário; Garcia, Catarina; Alopaeus, Julia; Molpeceres, Jesus; Hagesaether, Ellen; Tho, Ingunn; Rijo, Patrícia; Reis, Catarina
Abstract: Glycyrrhiza glabra L. is considered an important source of bioactive compounds. This study aimed at the development of an efficient solution for the treatment of oral candidiasis. Several extracts of Glycyrrhiza glabra L. were prepared using different solvents and their potential in vitro antifungal activity was assessed. Ethanolic extracts showed the most promising results against C. albicans. This extract was incorporated into mucoadhesive nanoparticles (PLA, PLGA and alginate), which were further included in an oral gel, an oral film and a toothpaste, respectively. The results showed that nanoparticles were successfully produced, presenting a mean size among 100–900 nm with high encapsulation efficiency. In vitro studies showed that the most bioadhesive formulation was the oral film with extract-loaded PLGA nanoparticles, followed by the toothpaste with extract-loaded alginate nanoparticles and the oral gel with extract-loaded PLA nanoparticles.